Income inequality in non-communicable diseases mortality among the regions of the Slovak Republic - Gavurová, Beáta; Kováč, Viliam; Šoltés, Michal; Kot, Sebastian; Majerník, Jaroslav (Central European Journal of Public Health, 2017)
AIM: A great amount of non-communicable disease deaths poses a threat for all people and therefore represents the challenge for health policy makers, health providers and other health or social policy actors. The aim of this study is to analyse regional differences in non-communicable disease mortality in the Slovak Republic, and to quantify the relationship between mortality and economic indicators of the Slovak regions. METHODS: Standardised mortality rates adjusted for age, sex, region, and period were calculated applying direct standardisation methods with the European standard population covering the time span from 2005 to 2013. The impact of income indicators on standardised mortality rates was calculated using the panel regression models. RESULTS: The Bratislava region reaches the lowest values of standardised mortality rate for non-communicable diseases for both sexes. On the other side, the Nitra region has the highest standardised mortality rate for non-communicable diseases. Income quintile ratio has the highest effect on mortality, however, the expected positive impact is not confirmed. Gini coefficient at the 0.001 significance level and social benefits at the 0.01 significance level look like the most influencing variables on the standardised mortality rate. By addition of one percentage point of Gini coefficient, mortality rate increases by 148.19 units. When a share of population receiving social benefits increases by one percentage point, the standardised mortality rate will increase by 22.36 units. CONCLUSIONS: Non-communicable disease mortality together with income inequalities among the regions of the Slovak Republic highlight the importance of economic impact on population health.
Keywords: Noncommunicable Diseases; Sex Factors; věkové faktory; Slovakia; lidé; Slovenská republika; neinfekční nemoci; mužské pohlaví; příjem; socioekonomické faktory; Female; Male; sexuální faktory; Age Factors; Income; Socioeconomic Factors; ženské pohlaví; Humans